2012
DOI: 10.3390/f3030684
|View full text |Cite
|
Sign up to set email alerts
|

Leaf Physiological and Morphological Responses to Shade in Grass-Stage Seedlings and Young Trees of Longleaf Pine

Abstract: Abstract:Longleaf pine has been classified as very shade intolerant but leaf physiological plasticity to light is not well understood, especially given longleaf pine's persistent seedling grass stage. We examined leaf morphological and physiological responses to light in one-year-old grass-stage seedlings and young trees ranging in height from 4.6 m to 6.3 m to test the hypothesis that young longleaf pine would demonstrate leaf phenotypic plasticity to light environment. Seedlings were grown in a greenhouse un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 48 publications
1
6
0
Order By: Relevance
“…Studies on leaf functional traits have contributed to the understanding of plant adaptation to changing environments. Previous studies indicated that specific leaf area increased with decreasing light exposure 5,6 , leaf thickness increased due to intense irradiance 7 , the thickness of palisade tissue decreased and that of spongy tissue increased under weak lighting conditions 8 , and higher maximum stomatal conductance may benefit species under low CO 2 conditions and high irradiance or nutrient supply 9 . Cornwell, et al .…”
Section: Introductionmentioning
confidence: 98%
“…Studies on leaf functional traits have contributed to the understanding of plant adaptation to changing environments. Previous studies indicated that specific leaf area increased with decreasing light exposure 5,6 , leaf thickness increased due to intense irradiance 7 , the thickness of palisade tissue decreased and that of spongy tissue increased under weak lighting conditions 8 , and higher maximum stomatal conductance may benefit species under low CO 2 conditions and high irradiance or nutrient supply 9 . Cornwell, et al .…”
Section: Introductionmentioning
confidence: 98%
“…The HN and MN rates used in this study [24] and by Jackson et al [38] produced seedlings with higher foliar N concentrations than seedlings given an extra fall fertilization of ammonium nitrate in a study by Rodríguez-Trejo et al [57] (0.9%). Our October concentrations of foliar N ( Table 4) were between those observed in greenhouse-grown (2.6%) and field-grown (0.75%) longleaf pine [58]. During the second field season, our seedling fascicles had concentrations of N, Mg, and Ca similar to, and P and K higher than, those of longleaf pine fascicles six years after outplanting in central Louisiana [32].…”
Section: Mineral Nutritionmentioning
confidence: 45%
“…For comparison, the Levenberg-Marquardt (LM) algorithm, a derivative based local optimization method, was also applied to estimate parameters of the photosynthetic models. The raw data of species 2, 5–9, 14–17, 20 and 22 (see Supplementary Table S4 ) were extracted from figures in publications 25 26 27 28 29 30 31 32 33 34 35 36 using the GetData Graph Digitizer 2.26 ( http://getdata-graph-digitizer.com ). After 500 iterations, the estimates from the three optimization methods were used to evaluate their performance.…”
Section: Methodsmentioning
confidence: 99%